Arbuscular mycorrhizal fungi increase aleurone layer zinc concentration but reduce overall zinc bioavailability in rice grain - Thi Diem Nguyen; Na Sai; Alexander A. T. Johnson; Enzo Lombi; Euan Smith; Casey L. Doolette; Timothy R. Cavagnaro; Stephanie J. Watts‐Williams (Plants, People, Planet)
Societal Impact Statement Rice is a critical crop for the delivery of calories and essential micronutrients to the human diet. Biofortification of rice with zinc (Zn) and iron (Fe) aims to combat the health issues associated with “hidden hunger”. Arbuscular mycorrhizal (AM) fungi have been explored for their potential to enhance Zn and Fe uptake in rice products. However, phytate, an anti‐nutritional compound rich in phosphorus (P), reduces the bioavailability of Zn and Fe in cereals. We investigated how AM fungal uptake of Zn, Fe and P interacts to affect bioavailability in rice and found mycorrhizal rice tends to have lower micronutrient bioavailability than non‐mycorrhizal. Summary Micronutrients such as zinc (Zn) and iron (Fe) play a crucial role in human health. In humans, the ability for micronutrients to be absorbed in the human digestive system (i.e., bioavailability) is hindered by phytate. Accumulation of phytate in the aleurone layer of cereal grains is affected by soil characteristics, particularly the availability of phosphorus (P). Arbuscular mycorrhizal (AM) fungi take up great amounts of P, but also some Zn and Fe into the host plant. In this study, we explored how AM fungi and soil P impact grain gene expression and bioavailability of Zn and Fe in rice under aerobic, controlled‐environment growing conditions. Five rice varieties were grown with or without AM fungal inoculation (Rhizophagus irregularis), under two soil P availabilities. Samples of developing grain were taken for RNAseq analysis. At plant maturity, grain nutrition was examined on a total concentration basis, and specifically in the aleurone layer by Synchrotron x‐ray fluorescence microscopy. The effect of AM fungi on Zn and Fe concentration was positive when only the aleurone layer was considered, but negative for whole grain concentrations. The AM‐colonised plants also accumulated more phytate in their grain compared to the non‐AM plants, leading to lower overall Zn bioavailability. Indirect effects of AM fungi on grain gene expression were small. The impact of AM colonisation on the bioavailability of Zn and Fe in rice was dependent on whether the whole grain, or specifically the aleurone layer, were quantified. This has implications for the consumption of whole vs milled rice products for humans.